2015
DOI: 10.1002/ange.201502302
|View full text |Cite
|
Sign up to set email alerts
|

Where is the Oxygen? Structural Analysis of α‐Humulene Oxidation Products by the Crystalline Sponge Method

Abstract: Crystal structures of a-humulene,acyclic sesquiterpene,a nd its oxidized subproducts,w ere analyzed by the crystalline sponge method. Regio-and stereochemistry,including absolute configuration when achiral oxidant was applied, and the stable conformations of all the scaffold-related compounds were successfully determined for samples on a 5-50 mgscale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…As tereospecific 1,2-alkyl shift of secondary Alternatively,i ti sp erhaps more likely that carbocation 14 would directly rearrange to give carbocation 16 through ac oncerted, asynchronous alkene cyclization/1,2-alkyl shift. As expected from molecular modelling studies and Fujitas humulene epoxidation work, [8] treatment of 1 with m-CPBAg enerated epoxide 13 as as ingle diastereomer in 76 %yield through diastereoselective oxidation of the D 8,9 alkene.W ew ere then delighted to observe that acid-Scheme 1. [9] Theprimary aim of this project was to use the biosynthetic hypothesis outlined in Scheme 1a st he blueprint for ad ivergent, biomimetic synthesis of hyperjaponols A-C (6-8)f rom hyperjapone A( 1).…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…As tereospecific 1,2-alkyl shift of secondary Alternatively,i ti sp erhaps more likely that carbocation 14 would directly rearrange to give carbocation 16 through ac oncerted, asynchronous alkene cyclization/1,2-alkyl shift. As expected from molecular modelling studies and Fujitas humulene epoxidation work, [8] treatment of 1 with m-CPBAg enerated epoxide 13 as as ingle diastereomer in 76 %yield through diastereoselective oxidation of the D 8,9 alkene.W ew ere then delighted to observe that acid-Scheme 1. [9] Theprimary aim of this project was to use the biosynthetic hypothesis outlined in Scheme 1a st he blueprint for ad ivergent, biomimetic synthesis of hyperjaponols A-C (6-8)f rom hyperjapone A( 1).…”
mentioning
confidence: 53%
“…Further racemic natural products,hyperjaponols A-C [2] (6)(7)(8), have also been isolated from Hypericum japonicum.T he most structurally intriguing of these natural products is hyperjaponol C( 8)b ecause its stereochemically complex, but racemic, trans-isodaucane framework implies ah ighly predisposed, non-enzymatic biosynthesis. Further racemic natural products,hyperjaponols A-C [2] (6)(7)(8), have also been isolated from Hypericum japonicum.T he most structurally intriguing of these natural products is hyperjaponol C( 8)b ecause its stereochemically complex, but racemic, trans-isodaucane framework implies ah ighly predisposed, non-enzymatic biosynthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This activity stemsp artly from the chemist's desire to understand the self-assembly of complex multi-component architectures, [1] but also from the fact that the resultinga ssemblies can be discrete [1] or polymeric [2] in nature,p ossessing targeted physical properties [3] or finding utility in aw ide variety of areas such as catalysis, [4] controlled guest uptake/release [5] and novelc rystallisation media. [6] Strategies for directeda ssemblyt ypically rely on the use of both coordination templates and ligand design, [7] the latter being the general focuso ft his contribution.…”
mentioning
confidence: 99%
“…The [Mn III 2 Mn II 2 (C[4]) 2 ]s ingle-molecule magnet (SMM) [9b] was selected as the standardt est system to see if this would form without the xylyl-tether constraints discussed above.R eaction between benzyl-C [4] and manganese(II) chloride hydrate in aD MF/MeOH mixture and in the presence of triethylamine afforded ad ark purple solution from whichs ingle crystals grew upon vapour diffusion with acetonitrile. The crystalsw ere in at riclinic cell and structural studies found them to be [Mn III 2 Mn II 2 (benzyl-C[4]) 2 (OH) 2 (DMF) 6 ]·(MeOH) 0.6 (MeCN) 1.4 , 4,w ith structure solution being performedi nt he space group P-1. The asymmetric unit (ASU)c omprises one half of the expected Mn III 2 Mn II 2 butterfly-like cluster and symmetry generation Figure 1A).…”
mentioning
confidence: 99%